2014
DOI: 10.1016/j.sbspro.2014.11.075
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Voluntary Disclosure Practices of Banks in Bangladesh

Abstract: This study aims to explore the corporate voluntary disclosure practices of the listed banks in an emerging economy namely Bangladesh. Results show that the extent of voluntary disclosure significantly improves from 2005 to 2008. However, the level of disclosure items related to corporate governance and risk management are lower than other disclosure categories. Overall findings of this study contribute in the accounting and economic literature by adding an empirical results of voluntary disclosure of a highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Banks contribute to the economic development of countries through creating a financial infrastructure that enables the functioning and development of individuals and businesses. Al Mamun and Kamardin (2014) emphasised that banks play the major role by supplying funds to corporates, especially in the emerging economies where the capital market is yet to develop, and banks supply most of the capital. Additionally, society expects banks to participate in social welfare.…”
Section: Csr Disclosures In the Banking Sectormentioning
confidence: 99%
“…Banks contribute to the economic development of countries through creating a financial infrastructure that enables the functioning and development of individuals and businesses. Al Mamun and Kamardin (2014) emphasised that banks play the major role by supplying funds to corporates, especially in the emerging economies where the capital market is yet to develop, and banks supply most of the capital. Additionally, society expects banks to participate in social welfare.…”
Section: Csr Disclosures In the Banking Sectormentioning
confidence: 99%
“…In economic development, the financial information itself cannot depict corporate behavior very well, so the non-financial information, for example, CSR information, becomes a beneficial complement [27]. Mamun et al (2014) [28] found that banks have increasingly disclosed their CSR information in recent years. Theoretically, corporations disclose their CSR information voluntarily, mainly to meet their stakeholder's demands, releasing the information asymmetry between shareholders and managers, and reducing financing costs [2].…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Comprehensive research has been carried out over the years both in the developed and developing countries to measure the corporate voluntary disclosures by service and manufacturing companies (Singhvi & Desai, 1971;Buzby, 1974;Kahl & Belkaoui, 1981;Cooke, 1992;Malone et al, 1993;Hossain et al, 1994;Ahmed & Nicholls, 1994;Inchausti, 1997;Brown & Degaan, 1998;Haniffa & Cooke, 2002;Akhtaruddin et al, 2009;Hossain & Hammami, 2009;Mamun & Kamardin, 2014). Depoers (2000) conveyed that the concept of voluntary information has to be defined in relation to the right to information of one or numerous types of stakeholders: 'An item of information is considered as discretionary whenever it goes beyond the compulsory information for shareholders.…”
Section: Voluntary Disclosurementioning
confidence: 99%